1927 Ga. Laws 83, No. 398, § 2, ¶ 86 - (:unkn) unknown (General Publisher, 1927)
Levied a tax on dealers “in or near towns or cities” who deal “in pistols or in toy pistols which shoot cartridges, or who deals in pistol cartridges, or rifle cartridges, dirks, bowie knives, or metal knucks.”
--
Keywords: TAX - DEALERS